PERANCANGAN ULANG LAYOUT PROSES PRODUKSI PADA PT XYZ - Pratama, Andi Yuda; Arista, Anggia (Computer Science and Industrial Engineering, 2021)
To get high quality product can be influenced by the process flow and the layout of the production process facilities because planning and factory layout arrangements are the basis of the industrial world. Many problems that occur are caused by bad layout, such as loss of material handling costs and production processing time. It happens at PT XYZ where the work station layout has not taken into account the degree of closeness of the product process flow which has an impact on cost material handling to be large so it is necessary to redesign a new layout to rearrange the flow of material traffic according to product flow. To improve the layout of the work station in this research using the From to Chart method, the Activity Relationship Chart (ARC) which is applied with the Blocplan algorithm. The results showed that the best layout is the initial layout at this time material handling distance is 257,040 meters per year. In the new layout design, there is a total moment of 158,628 meters per year, so that the reduction in material handling mileage is 98.4128 meters per year or equal to 38,28% more effectively